Density distribution of receptors for peannut lectin in the structure of wall rats’ pharynx in the postnatal period after antenatal antigen influence - Voloshin M.A.; Matveyshina T.M. (Морфологія, 2012)
It was determined that in animals with antenatal antigen influence density peanut lectin receptors on the membrane and in the cytoplasm of epithelial cells mucus layer of the pharynx′ nasal part on the first day of life less in comparison intact animals group. Starting from the third day of life, the intensity of deposition benzydyn mark in epithelial cells cytoplasm of the upper and lower walls of the pharynx’ nasal part, and the secret of goblet cells in experimental animals is higher than in intact rats. Content carbohydrate residues β-D-galactose in the intercellular substance of submucous connective tissue of the pharynx above in experimental animals compared with intact during all periods of observation. Antenatal antigen influence leads to an increase in PNA+-lymphocytes in the mucous layer of the pharynx.